2018
DOI: 10.1088/1361-6463/aae41d
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory motion of a droplet in an active poroelastic two-phase model

Abstract: The onset of self-organized droplet motion is studied in a poroelastic two-phase model with free boundaries and substrate friction. In the model, an active, gel-like phase and a passive, fluid-like phase interpenetrate on small length scales. A feedback loop between a chemical regulator, mechanical deformations, and induced fluid flow gives rise to oscillatory and irregular droplet motion accompanied by spatio-temporal contraction patterns inside the droplet. By numerical simulations in one spatial dimension, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
29
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 57 publications
5
29
2
Order By: Relevance
“…flows give rise to pattern formation in a resting droplet [37]. In [38], we have studied 49 this model with free boundary conditions and linear friction between droplet and 50 substrate. While we were able to observe back and forth motion of the boundaries, the 51 center of mass (COM) position remained fixed.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…flows give rise to pattern formation in a resting droplet [37]. In [38], we have studied 49 this model with free boundary conditions and linear friction between droplet and 50 substrate. While we were able to observe back and forth motion of the boundaries, the 51 center of mass (COM) position remained fixed.…”
mentioning
confidence: 99%
“…52 Moreover, we derived an argument that COM motion is impossible with a spatially 53 homogeneous substrate friction. Furthermore, numerical simulations have shown that 54 an additional mechanism establishing an axis of polarity that is stable on long 55 timescales is necessary for net motion [38]. 56 In this work, we proceed in two steps.…”
mentioning
confidence: 99%
See 3 more Smart Citations